Behaviour of the F1-region, and Esand spread-F phenomena at European middle latitudes, particularly under geomagnetic storm conditions - F. Märcz (Annals of Geophysics, 2004)
Knowledge of the ionospheric electron density distribution and its fluctuations is essential for predicting ionospheric characteristics for radio wave propagation and for other applications such as satellite tracking, navigation, etc. Geomagnetic storm is the most important source of the ionisation density perturbatio ns. Recent studies of the F1-region electron density distribution revealed systematic seasonal and latitudinal differences in the F1-layer response to geomagnetic storm. At European higher middle latitudes no significant effect has been observed in summer and spring at heights of 160-190 km, whereas well-pronounced depression appears in winter and late autumn at least at 180- 190 km. A brief interpretation of this finding will be presented. On the other hand, the pattern of the response of the ionosphere at F1-layer heights does not seem to depend on the type of response of F2-layer (foF2) or on solar activity. Concerning the main types of ionospheric irregularities sporadic E and spread-F, it has been found that considering sporadic E-layers as thin diffraction screen, it may be modelled for propagation of radio-waves by the determination of the temporal variation of foEs representing in ionograms the mean ion density of «patches» of increased ion density embedded in the Es-layer. Spectrum of these variations indicates the mean period of the variations, which multiplied by the wind velocity gives the mean distance of patches, that is, the mean distance between the screen points. In case of spread-F, it has been found that irregularities causing spread-F are mostly due to plasma instabilities, though the role of travelling ionospheric disturbances may be not entirely neglected.